Fat grafts show higher hypoxia, angiogenesis, adipocyte proliferation, and macrophage infiltration than flaps in a pilot mouse study - Thomas, Benjamin; Warszawski, Jan; Falkner, Florian; Bleichert, Sonja; Haug, Valentin; Bigdeli, Amir Khosrow; Schulte, Matthias; Hoffmann, Sabrina H. L.; Garvalov, Boyan K.; Schreiber, Caroline; Takamiya, Masanari; Sleeman, Jonathan P.; et al. (Plastic and reconstructive surgery, 2023)
Background: - Over 137,000 breast reconstructions are performed annually by American Society of Plastic Surgeons (ASPS) members. Vascularized flaps and avascular lipofilling each account for over 33,000 autologous reconstructions. Although clinical and experimental observations suggest biologic differences with diverging effects on locoregional tumor control, comparative animal models are lacking. The authors standardized existing techniques in immunocompetent mice, laying the foundation for in vivo models of autologous breast reconstruction combinable with orthotopic tumor implantations. - Methods: - Twenty-five groin flaps and 39 fat grafts were transferred in female BALB/c-mice. Adipocytes were tracked via Hoechst-Calcein-DiI staining (n = 2 per group), and postoperative volume retentions were compared via magnetic resonance imaging (n = 3 per group) on days 1, 11, 21, and 31. Proliferation indices, microvessel densities, tissue hypoxia, and macrophage infiltrates were compared via Ki67, CD31, pimonidazole, and hematoxylin-eosin staining on days 5, 10, 15, 20, and 30 (n = 4 per group). - Results: - Viable adipocytes were present in both groups. Graft volumes plateaued at 42.7 ± 1.2% versus 81.8 ± 4.0% of flaps (P < 0.001). Initially, grafts contained more hypoxic cells (day 5: 15.192 ± 1.249 versus 1.157 ± 192; P < 0.001), followed by higher proliferation (day 15: 25.2 ± 1.0% versus 0.0 ± 0.0%; P < 0.001), higher microvessel numbers (day 30: 307.0 ± 13.2 versus 178.0 ± 10.6; P < 0.001), and more pronounced macrophage infiltrates (graded 3 versus 2; P < 0.01). - Conclusion: - This comparative murine pilot study of vascularized flaps versus avascular lipofilling suggests differences in volume retention, proliferation, angiogenesis, hypoxia, and inflammation. - Clinical Relevance Statement: - The biological differences of fat grafting versus flap transfer are not fully understood because no single comparative experimental model has been established to date. The authors present the first comparative small animal model of both techniques, which will allow the gaining of deeper insights into their biological effects.
Gesehen am 15.08.2024